TESTING FOR BACTERIAL CONTAMINATION ON CHICKEN (Gallus gallus domesticus) IN THE TRADITIONAL MARKET OF SOUTH LANGOWAN DISTRICT - Sambeka, Delvino; Mege, Revolson; Setyawati, Iriani; Lawalata, Helen J; Rompas, Christny Ferdina Evie (Universitas Negeri Manado, 2024)
Chicken meat (Gallus gallus domesticus) plays an important role in society with its role as one of the sources of fulfillment of animal protein in Indonesia. With the high consumption of chicken meat by the public, the hygiene and safety of chicken meat must be ensured so as not to incur losses to the people. This study aimed to determine the bacterial contamination based on the testing of Total Plate Counts, Coliform, Escherichia coli, and Salmonella sp. Meet the requirement of the Indonesian National Standard on chicken meat in the traditional market of Langowan Selatan District. The method used in this research is a descriptive method to analyze and describe the results of the study, the testing using several indicators to directly conclude bacterial contamination. The results of the total plate count bacterial contamination test of the colonies, TPC in sample 1 = 29,1xÃ‚Â kol/, sample 2 = 29,4xÃ‚Â kol/, sample 3 = 27,7xÃ‚Â kol/. MPN of Coliform and Escherichia coli results obtained in samples S1, S2, and S3 are 11xÃ‚Â kol/gr. The results of microbact Salmonella sp. In samples S1 are positive, and S2 and S3 are negative. Based on observations, it is suspected that contamination occurs because sellers use equipment that is less sterile and there is no cover or barrier so the chicken meat is in direct contact with the air and customer. It is concluded that based on bacterial testing indicators, chicken meat in the traditional market of Langowan Selatan District has exceeded the limit of SNI 7388 2009 and is contaminated.